Do screening and a randomized brief intervention at a Level 1 trauma center impact acute stress reactions to prevent later development of posttraumatic stress disorder?. Issue 3 (September 2018) - Manser, Stacey Stevens; Houck, Katherine; Kramer, Mark D.; Tabas, Irene A.; Brown, Carlos V.R.; Coopwood, Ben
Abstract : BACKGROUND: Approximately 20% to 40% of trauma survivors experience posttraumatic stress disorder (PTSD). The American College of Surgeons Committee on Trauma reports that early screening and referral has the potential to improve outcomes and that further study of screening and intervention for PTSD would be beneficial. This prospective randomized study screened hospitalized patients for traumatic stress reactions and assessed the effect of a brief intervention in reducing later development of PTSD. METHODS: The Primary Care PTSD (PC-PTSD) screen was administered to admitted patients. Patients with symptoms were randomized to an intervention or control group. The brief intervention focused on symptom education and normalization, coping strategies, and utilizing supports. The control group received a 3-minute educational brochure review. Both groups completed in-hospital interviews, then 45- and 90-day telephone interviews. Follow-up collected the PTSD checklist-civilian (PCL-C) assessment and qualitative data on treatment-seeking barriers. RESULTS: The PC-PTSD screen was successful in predicting later PTSD symptoms at both 45 days ( β = 0.43, p < 0.001) and 90 days ( β = 0.37, p < 0.001) even after accounting for depression. Correlations of the intervention with the PCL-C scores and factor score estimates did not reach statistical significance at either time point ( p = 0.827; p = 0.838), indicating that the brief intervention did not decrease PTSD symptoms over time. Of those at or above the PCL-C cutoff at follow-ups, a minority had sought treatment for their symptoms (43.2%). Primary barriers included focusing on their injury or ongoing rehabilitation, financial concerns, or location of residence. CONCLUSION: The PC-PTSD screen identified patients who later assess positive for PTSD using the PCL-C. The brief intervention did not reduce 45- and 90-day PTSD development. Follow-up interviews revealed lack of treatment infrastructure in the community. It will be important for trauma centers to align with community resources to address the treatment needs of at-risk patients. LEVEL OF EVIDENCE: Prospective randomized controlled trial, level II.